An assessment of nursing mothers' and young people's access to proprietary and patent medicine vendors' services in rural communities of south-eastern Nigeria: implication for review of national drug policy - C. J. Uneke; I. Obeka; B. I. Uneke; A. Umeokonkwo; C. A. Nweze; K. I. Otubo; O. E. Uguru (Taylor & Francis Group, 2021)
Background Patent and proprietary medicine vendors (PPMVs) form part of the informal healthcare system and are the first point of call for 75% of Nigerians who live in rural and underserved areas where there is limited access to healthcare services. This group of healthcare providers are located close to communities and are easily accessible to the people. This study seeks to determine how PPMVs influence access to medicines among nursing mothers and young people and how this progresses South Eastern Nigeria towards universal health coverage. Methods A cross-sectional descriptive study was conducted using a purposive sampling technique. Two slightly different pre-tested and validated 5-point Likert scale questionnaires were used to survey the nursing mothers and young people (18-20 years old). The questionnaire for nursing mothers assessed the perception regarding PPMV services and community access to medicines used for the treatment of childhood infections. The questionnaire for young people assessed the services rendered by the PPMVs including family planning, and major enablers/barriers towards to access to medicine. Results A total of 159 nursing mothers and 148 youths participated in the study. Up to 60% of both population had a minimum of secondary school qualification. About 90% of the nursing mothers were married and 88% were nursing babies from 1 to 12 months. Results show that the PPMVs were the first point of call for healthcare needs among the respondents and they are easily accessible and sell affordable medicines. The nursing mothers frequently treat their children's cough with antibiotics with a mean rating (MNR) of 4.7 out of 5 points and most source these antibiotics from PPMV shops. Up to 90% of the nursing mothers reported that the children got well after the treatment. The drugs mostly purchased by the youths from the PPMVs included antimalarials (95%), analgesics (87.7%) and antibiotics (81.3%). Only 25.5% of the respondents purchased family planning commodities. Most of the respondents sought health care from PPMVs with a MNR of 3.4. Patronage of PPMVs for and usage of family planning products by the respondents had MNRs ranging from 1.4 to 1.8. Conclusion PPMVs are bridging the gap in healthcare delivery in the rural and underserved areas. Training of this group of practitioners and appropriate monitoring will go a long way in ensuring that the services they render are efficient, effective and improve the health indices in a low-income setting.